Innovation and Technology in Sports: Proceedings of the International Conference on Innovation and Technology in Sports, (ICITS) 2022, Malaysia - Syed Faris, Syed Omar (Springer Singapore, 2023)
This book presents the proceedings of ICITS 2022 covering different tracks in the field of Sports Engineering and Technology, namely, Instrumentation, Materials, Data Analytics, Biomechanics, Simulation, Equipment Design and Performance Analysis, amongst others. This collection of articles deliberates the key challenges as well as technological innovations that facilitate the enhancement of sporting performance. The readers are expected to gain an insightful view on the current trends, issues, mitigating factors, technological innovations as well as proposed solutions.